Revisiting the Domestication Process of African Vigna Species (Fabaceae): Background, Perspectives and Challenges - Davide Panzeri; Werther Guidi Nissim; Massimo Labra; Fabrizio Grassi (Plants, 2022)
Legumes are one of the most economically important and biodiverse families in plants recognised as the basis to develop functional foods. Among these, the Vigna genus stands out as a good representative because of its relatively recent African origin as well as its outstanding potential. Africa is a great biodiversity centre in which a great number of species are spread, but only three of them, Vigna unguiculata, Vigna subterranea and Vigna vexillata, were successfully domesticated. This review aims at analysing and valorising these species by considering the perspective of human activity and what effects it exerts. For each species, we revised the origin history and gave a focus on where, when and how many times domestication occurred. We provided a brief summary of bioactive compounds naturally occurring in these species that are fundamental for human wellbeing. The great number of wild lineages is a key point to improve landraces since the domestication process caused a loss of gene diversity. Their genomes hide a precious gene pool yet mostly unexplored, and genes lost during human activity can be recovered from the wild lineages and reintroduced in cultivated forms through modern technologies. Finally, we describe how all this information is game-changing to the design of future crops by domesticating de novo.